2019
DOI: 10.1039/c9md00154a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a hybrid gene cluster to reveal coupled ring formation–hydroxylation in the biosynthesis of HSAF and analogues from Lysobacter enzymogenes

Abstract: HSAF and analogues are polycyclic tetramate macrolactams (PoTeMs) isolated from Lysobacter enzymogenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 18 publications
0
27
1
Order By: Relevance
“…These observations further highlight the importance of Streptomyces species as prolific sources for bioactive compounds and they indicate the worth of genome mining in marine-derived Streptomycetes [35]. Similar to the well-established biosynthetic pathway for 5/5/6 type of PTMs [20,23,33], PtmA catalyzes the formation of a common polyene tetramate precursor, which is sequentially cyclized by PtmB2 /PtmB1 into an intermediate with the 5/5 carbocyclic ring system (Figure 2b). It has been hypothesized that OX3, which is a PtmB2 homologous enzyme, is involved in controlling the formation of products with both cisand trans-orientated H-10/H-11 in HSAF (7) biosynthesis [23].…”
Section: Biosynthetic Implicationsmentioning
confidence: 60%
See 2 more Smart Citations
“…These observations further highlight the importance of Streptomyces species as prolific sources for bioactive compounds and they indicate the worth of genome mining in marine-derived Streptomycetes [35]. Similar to the well-established biosynthetic pathway for 5/5/6 type of PTMs [20,23,33], PtmA catalyzes the formation of a common polyene tetramate precursor, which is sequentially cyclized by PtmB2 /PtmB1 into an intermediate with the 5/5 carbocyclic ring system (Figure 2b). It has been hypothesized that OX3, which is a PtmB2 homologous enzyme, is involved in controlling the formation of products with both cisand trans-orientated H-10/H-11 in HSAF (7) biosynthesis [23].…”
Section: Biosynthetic Implicationsmentioning
confidence: 60%
“…It should be noted that a trans-orientation of H-10 and H-11 was assigned for 1, because of the obvious NOESY correlations of H-8/H-10, H10/H-12, and H-11/H-29b ( Figure 3). Previously, a trans-orientation of H-10 and H-11 was reported for pactamide A [20], aburatubolactam A (X-ray crystallography structure available [31]), combamide D [32], deOH alteramides, and lysobacterene B [33]. In the recently reported 5/5 type of PTMs umezawamides, the relative orientation of H-10 and H-11 was not determined [34].…”
Section: Genome Mining Of a Ptm Biosynthetic Gene Clustermentioning
confidence: 96%
See 1 more Smart Citation
“…SGR812 or PtmB2 or OX3 was demonstrated to catalyze the formation of the first five-membered ring [ 8 , 30 ], whereas the formation of the second five-membered ring appeared to be catalyzed by SGR813 or PtmB1 or OX1/OX2 [ 8 , 30 ]. Notably, it has been confirmed that formation of the second ring is coupled to C14 hydroxylation during HSAF biosynthesis [ 33 ]. The presence of two oxidoreductases in the sko gene cluster is consistent with the 5/5 ring system seen in 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The lafE (OX3) gene product is responsible for the formation of the first pentameric ring, while genes lafC (OX1) and lafD (OX2) are involved in the formation of the second pentameric ring, and lafF (OX4) mediates the formation of the hexameric ring (Li et al ., 2014). The ftdA gene (ORF7) encoding a homologue of a sterol desaturase is responsible for 3‐hydroxylation of the polycyclic tetramate macrolactam structure (Li et al ., 2019).…”
Section: Hsaf the Long‐range Antifungal Weapon Of L Enzymogenesmentioning
confidence: 99%